EFEKTIVITAS TEKNIK VISUALISASI TERHADAP KEPERCAYAAN DIRI PEMAIN TENIS MEJA - Kembaren, Aby Girl (Hanoman Journal: Physical Education and Sport, 2024)
Table tennis is a popular and competitive sport throughout the world. Playing table tennis requires high speed, accuracy, concentration and reflexes. Apart from the physical aspect, the mental aspect is also an important part of the preparation of table tennis athletes, especially the confidence to manage pressure and stress in matches. Visualization is considered an important mental training technique for table tennis athletesÂ to improve performance and self-confidence. This research aims to identify the effectiveness of visualization techniques on the self-confidence of table tennis players. The research method used is a qualitative descriptive method through literature study sourced from journals, scientific articles, books and other relevant sources. The results of this study show that visualization techniques have proven effective in increasing the self-confidence of table tennis players as evidenced by a significant increase in self-confidence test scores. Visualization techniques can help table tennis players to be more confident in their abilities and reduce feelings of anxiety or fear. Additionally, visualization techniques can help table tennis players more easily overcome mistakes and bounce back from failure. Mainly about the players' self-confidence which has also increased sharply.